Oxidation Kinetics of Simvastatin Using Cetyltrimethylammonium Dichromate. Issue 4 (5th December 2012) - Sahoo, Prangya Rani; Patel, Sabita; Mishra, B. K.
ABSTRACT This article reports an attempt on the studies on resistance of oxidative stress by the prodrug, simvastatin (SV). Cetyltrimethylammonium dichromate has been used as a lipid compatible oxidant to study the oxidation kinetics of SV in organic media. The reaction undergoes via an ionic mechanism without any side product. The reaction is found to be acid catalyzed and sensitive to solvent polarity. The increase in the rate constant due to an increase in hydrophobicity (apolarity) of the solvent indicates the existence of a less polar transition state. Furthermore, the decrease in the rate constant due to an increase in [CTAB] suggests partitioning of the substrates and the oxidants into two different domains with different polar characteristics akin to a reversed micellar aggregates. Considering the above results and the thermodynamic parameters, a reaction mechanism has been proposed, wherein a complex formed at the interface of the two domains due to the reactant and the oxidant in a fast process decomposes to the products in a slow process in the nonpolar bulk.